The effects of adding molasses and inoculant to silages of fodder pea and rye grass in different proportions on silage quality - Şen, G; Evci, Ş; Kara, K; Kara, K; Erol, T (Journal of the Hellenic Veterinary Medical Society, 2024)
The aim of this study was to determine the effects of adding melas and microbial inoculant to the mixed silages of different proportions fodder pea (FP) and rye grass (RG) grown in arid conditions on silage quality and in vitro digestibility. For this purpose, silages containing fodder pea and rye grass at 20, 40, 60 and 80% ratios were prepared in jars with additives 5% molasses and 10 g/t inoculant (1.25×1011 CFU/g) and waited 60 days. At the end of the study, among groups was determined a significant difference in the pH value, lactic acid (LA), acetic acid (AA) and ammonia-N levels of the mixed silages (p<0,05). It was determined that inoculant was effective on LA level (p<0,05). Mixture level x additive interaction was observed at pH value, LA, and ammonia-N levels (p<0.05). In vitro digestibility, energy values, and nutrient contents of silages showed significantly change among groups (p<0.05). While molasses significantly increased the dry matter levels, it decreased the acid detergent fiber (ADF) level (p<0.05). Mixture level x additive interaction was observed at only neutral detergent fiber (NDF) level (p<0.05). While the structure was positively affected in silages containing 80% FP, the Flieg score decreased in silages containing 60% FP (p<0.05). With addition of molasses increased the Flieg score of silages, and it had mixture level x additive interaction (p<0.05). As a result, although mix silages containing 80% FP had high ammonia-N, excellent fermentation was observed with low pH value and high LA level. In addition, although NDF and ADF levels increased, mix silages with FP at 80% levels have higher in vitro digestibility and energy levels. Each of additives had a positive effect on silages, but molasses was determined to be more effective.